355 MEASUREMENT OF OXIDATIVE STRESS IN A RAT MODEL OF NEPHROPATHY IN TYPE 2 DIABETES. Issue 1 (1st January 2007) - Patel, N.; Shi, S.; Nanua, S.; Simoni, J.; Prabhakar, S. S.
Abstract : Oxidative stress is strongly implicated in the pathogenesis of diabetic nephropathy (DN). However, mechanisms underlying oxidative stress remain incompletely understood. Furthermore, several markers of oxidative stress have been used, and the relative merits of these remain undetermined. To address that question, we compared two different parameters of oxidative stress, viz. 8-iso prostaglandin F2α or 8 isoprostane (a measure of lipid peroxidation) and 8-OH deoxyguanosine or 8-OHdG (a measure of DNA oxidation) serially in a new rat model of type 2 diabetes. ZSF rats were fed from the eighth to the fortieth week on a high-carbohydrate Purina 5008 diet to maintain hyperglycemia. The rats developed hypertension, hyperglycemia, proteinuria, and renal failure. Measures of renal function, blood pressure, and oxidative parameters were monitored at weeks 8, 20, and 40. Our data showed that although both 8-OHdG and 8 isoprostane were elevated in the urine at 20 weeks, only the former continued to increase until 40 weeks of age. Additionally, the levels of 8-OHdG correlated better with a decline im creatinine clearance, suggesting that 8OHdG may be a superior marker of oxidative stress in DN than 8 isoprostane.